The symbolism of the owl in ancient Greek thought - Obaid Al-Dalfi, Najm (Journal of College of Education, 2022)
The art of Different Greek sources remind us that animals were a familiar sight in the city of Athens and were associated with the behaviors and traits of gods, daily life, religious beliefs and myths. Owls are one of these interesting and symbolic animals scattered throughout many parts of prehistoric age to the present and in various fields, notably religion, art and economics, and that owls as a symbol associated with night, wisdom and evil did not receive the attention of studies. Hence my preoccupation with owls and their search for symbols and collective memory is because of their strength and preference over the ancient Greeks, and as they thought they were. This research revealed the symbolic meanings of the owl from its inception as a symbol of the goddess "Athens" and other symbolic meanings.